ĐA DẠNG THÀNH PHẦN LOÀI BỘ CÁ TRÍCH CLUPEIFORMES VÙNG ĐỒNG BẰNG SÔNG CỬU LONG - Nguyễn, Tuấn Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DIVERSITY OF FISH SPECIES COMPONENT IN THE ORDER CLUPEIFORMES IN THE MEKONG DELTAThe study was conducted in the Mekong Delta area, in two seasons: dry and rainy seasons, from June 2016 to December 2018. Fish samples were collected at 35 sites in the river tributaries of the Mekong Delta of Vietnam. The study results identified 22 species belonging to 3 families: Pristigasteridae, Clupeidae and Engraulidae. Fish species composition in the order Clupeiformes in study area is more than that in studies of recent authors in the Mekong Delta, such as: that is more than 01 family and 10 species compared to the study result of Thai Ngoc Tri (2015); more than 6 species and 01 species to the study result of Tran Trac Dinh (2013) and MRC (2015), respectively. However, in fact, except some species as Clupeichthys aesarnensis, Clupeoides borneensis and Coilia rebentischii have relatively high catches, the remaining species have negligible yields, and even some species was collected only 1 specimens during the study period, such as: Thryssa dussumieri and Thryssa setirostris. The species composition of fish in the order Clupeiformes is not significantly different between seasons; it is more than 01 species in the flood season compared with dry season. However, the number of specimens collected during the flood season is 1.3 times higher than the dry season. This is completely consistent with the biological characteristics, the distribution of species in this order.